Clinical Privilege for Nurse Anesthetist Viewed from a Legal Aspect - Sembiring, Tamaulina Br.; Rahmatika, Wahyu (Formosa Journal of Multidisciplinary Research, 2024)
Nurse Anesthetist has the authority to provide anesthesia services in preanesthesia, intraanesthesia, and postanesthesia. In terms of legal regulations, nurse anesthetist have clear regulations as a reference in carrying out their professional practice. However, in its implementation there are still health workers who work in anesthesia services who do not meet the statutory requirements based on competency, certification, registration and licensing as a nurse anesthetist which must be proven by having a nurse anesthetist Registration Certificate and a nurse anesthetist practices License. The aim of this research is to find out how Clinical Privilege for nurse anesthetist is viewed from a legal aspect. The research method uses a qualitative approach with a combined method of literature study and field study with Qualitative Descriptive Analysis Techniques.